Triple dehydrofluorination as a route to amidine-functionalized, aromatic phosphorus heterocycles. Issue 98 (10th November 2022) - Coles, Nathan T.; Groth, Lucie J.; Dettling, Lea; Frost, Daniel S.; Rigo, Massimo; Neale, Samuel E.; Müller, Christian
Abstract : Hitherto unknown amidine-functionalized phosphabenzenes selectively form by a cascade of dehydrofluorination reactions. Abstract : An unexpected route to hitherto unknown amidine-functionalized phosphinines has been developed that is rapid and simple. Starting from primary amines and CF3 -substituted λ 3, σ 2 -phosphinines, a cascade of dehydrofluorination reactions leads selectively to ortho -amidinephosphinines. DFT calculations reveal that this unusual transformation can take place via a series of nucleophilic attacks at the electrophilic, low-coordinate phosphorus atom.